Violence as a trigger for psychic illness in third-age women (Research, Society and Development, 2021)
The present study deals with an integrative bibliographic review on Violence as a trigger for psychological illness in elderly women. It aims to investigate the correlation between violence against elderly women and mental illness. Violence against the elderly refers to any action or omission performed in a public or private place that causes death, injury or physical or psychological pain. Elderly people become easy victims, often because they depend on their family members in numerous aspects and older women are the most vulnerable to domestic violence, the mistreatment they suffer contributes to their illness, including the psychological one. The study also sought to characterize female aging in Brazil; describe the situation of violence against women in the elderly; relate violence against women in the elderly and mental illness. Identifying and treating the diseases caused by this violence is one of the challenges, considering gender and age group. For the research, the databases of SCIELO, PUBMED and GOOGLE ACADEMIC were used in the years 2010 to 2020 for data analysis. The results show that violence is a determining factor for mental illness. Given the above, it is concluded that in relation to specific issues of mental health and domestic violence in the elderly, it is necessary to ask questions in order to make this violence more obvious, sensitize professionals, and conduct research to problematize the relationship between violence and psychological illnesses of elderly women, which can provide numerous contributions in this field.